מה זה (x ^ 3 + 4x ^ 2 + 6x + 4) -: (x + 2)?

מה זה (x ^ 3 + 4x ^ 2 + 6x + 4) -: (x + 2)?
Anonim

תשובה:

# (x ^ 3 + 4x ^ 2 + 6x + 4) = (x ^ 2 + 2x + 2) (x + 2) #

הסבר:

Ieties #f (x) = x ^ 3 + 4x ^ 2 + 6x + 4 # אנחנו יודעים את זה # x = -2 # הוא שורש למשוואה זו, כי #f (-2) = 0 #. לכן #f (x) = q (x) (x + 2) #. עכשיו מתחזה #q (x) = ax = 2 + bx + c # ואת equating #f (x) -q (x) (x + 2) = 0 # יש לנו:# (1-a) x ^ 3 + (4-2a-b) x ^ 2 + (6-2b-c) x + 4-2c = 0 #. מערכת יחסים זו חייבת להיות בטלה לכל #איקס# אז נקבל: #q (x) = x ^ 2 + 2x + 2 #